CLINICAL AND SUBCLINICAL STAPHYLOCOCCUS AUERUS IN DAIRY BUFFALOES: DISEASE CHARACTERISTICS AND ANTIBIOTIC SUSCEPTIBILITY PROFILES OF ISOLATES - A. Hussain; A. Shakoor; A. Yousaf; S. U. Rehman; M. A. Zaman (Journal of Animal and Plant Sciences, 2012)
This study was conducted to evaluate the disease characteristics of Staphylococcus aureus mastitis in buffaloes and antibiotic susceptibility of isolates. Visual inspection and palpation indicated as; hind quarters were asymmetric (n=2), udder and teat wounds (n=2), scar tissue (n=1), warts on teats (n=1) and all others parameters were normal. A total of 100 milk samples (20 clinical and 80 subclinical) from mastitic buffaloes were collected from different government and private livestock farms in and around Faisalabad. These samples were subjected to antibiotic susceptibility testing. Sixty isolates of Staphylocococci were obtained on the basis of growth on Staph-110 medium, colony morphology and haemolytic pattern on 5% sheep blood agar plates. All sixty isolates were gram positive and catalase positive. Of these, 23 were slide coagulase test, Tube coagulase test and Staphytect plus test positive and remaining 37 were negative. Those 23 were identified as Staphylococcus aureus (coagulase positive Staphylococci) and the remainder were coagulase negative Staphylococci. All these 23 isolates of Staphylococcus aureus were subjected to antibiotic sensitivity testing against the most commonly used antibiotics in mastitis (i.e. enroflaxacin, ciprofloxacin, chloramphenicol, amoxicillin, ampicillin, gentamycin, novobiocin, oxytetracycline and cotrimaxazole). The antibiogram study of these antibiotics in the form of their percent sensitivity was as co-trimoxazole (100%), oxytetracycline (95.65%), amoxicillin (86.95%), gentamicin (86.95), ampicillin (82.60 %), ciprofloxacin (82.60%), chloramphenicol (82.60%), enrofloxacin (69.56%) and novobiocin (60.86%).
Keywords: Mastitis; Staphylococcus aureus; Buffalo; antibiogram